Zinc-solubilizing bacterial consortia: a promising approach for zinc biofortification of crops - Upadhayay, Viabhav Kumar; Gangola, Saurabh; Taj, Gohar; Gaurav, Kumar; Rani, Anju; Kumar, Sunil; Garg, Shivanshu; Gupta, Gaurav; Ali, Haider; Siddiqui, Sazada; Alamri, Saad A. M.; Mittal, Amit; et al. (Frontiers in Microbiology, 2025)
The term “zinc-solubilizing bacteria” (ZSB) refers to a specific group of soil bacteria that are associated with zinc-solubilizing activity in the soil through a variety of mechanisms. The functional use of ZSB has been proposed for the zinc (Zn) biofortification of crops to address Zn malnutrition. The application of zinc-solubilizing bacterial inoculants that harbor significant plant probiotic traits offers an eco-friendly approach to producing crops with improved Zn content in various edible parts of plants. In soil, ZSB solubilize complex forms of Zn compounds by producing organic acids and employing other mechanisms (such as the secretion of “siderophore,” extrusion of “proton,” expression of “oxidoreductive systems” on cell membranes, and secretion of “chelated ligands”), making the resulting soluble form of zinc readily accessible to plants. ZSB also act as plant growth stimulators, demonstrating both direct and indirect mechanisms that promote robust plant growth. In recent years, the application of two or more ZSB strains in a consortium has gained attention as a cost-effective alternative for Zn biofortification. This approach may serve as a promising strategy for promoting plant growth and optimizing yield performance. This review discusses various methods of Zn biofortification, highlighting ZSB and their consortia in increasing Zn content in grains and other edible crop parts, as well as the mechanisms involved in Zn solubilization by these bacteria. This insight paves the way for developing eco-friendly strategies that integrate microbial-based solutions to improve crop nutrient bioavailability.